Waste Governance Through the "Waste to Energy" Program at the Final Processing Site of Talangagung Education Tourism in Malang Regency - Rika Puspita Dewi; Ali Roziqin (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2022)
This research aims to find out the governance at the Talangagung Education Tourism Final Processing Site (TPA) to overcome the waste problem. Waste is a community product that can cause environmental problems. Talangagung Educational Tourism Landfill, the largest landfill in Malang Regency has major challenges in waste management. The volume of waste at the Talangagung education tourism landfill every year continues to increase. Waste that is not managed properly will be based on the environment because it can cause pollution. This research is focused on waste to energy conducted by Talangagung Education Tourism Landfill in waste management. Paying attention to waste governance refers to Good Environmental Governance which involves all members of the public both from the government, the private sector, and the general public. This research uses qualitative descriptive methods with primary data through interviews and observations, as well as secondary data derived from research- related literature studies. The result in the implementation of waste governance at the Talangagung education tourism landfill with energy waste can meet the principles of good governance that produce benefits for the surrounding community. In conclusion, Talangagung Education Tourism Landfill can carry out waste governance with the latest energy for better environmental sustainability.